VAMOS FESTEJAR O DIVINO? AS CELEBRAÇÕES EM HONRA AO DIVINO ESPÍRITO SANTO NA CIDADE DE PONTA GROSSA 1882-2015 - Rocha, Vanderley de Paula (2016)
This dissertation focuses on religious practices, held in Ponta Grossa / PR, to honor the Holy Spirit. We focus in the demonstrations that took place in the House of the Divine, a place that won the title after Maria Julio Cesarino Xavier have housed inside the image representation of the Holy Spirit, a dove with outstretched wings, engraved on a piece of wood that you would find in a river . Thus, these manifestations are present in this city since 1882 prevailed until today. This paper discusses the relationships that men and women have established with the sacred through festive events in praise of the Divine and identify the position of local ecclesiastical authorities in relation to these practices developed by these faithful. Therefore, we use local newspapers as sources, festival programs and the owner of the tipping process (House of the Divine). The research found its theoretical foundations in Roger Chartier, Michel de Certeau, Pierre Bourdieu, Michel Vovelle and MirceaEliade